Bifurcated Degradative Pathway of 3-Sulfolactate in Roseovarius nubinhibens ISM via Sulfoacetaldehyde Acetyltransferase and (S)-Cysteate Sulfolyase - Denger, Karin (American Society for Microbiology (ASM), 2009)
Data from the genome sequence of the aerobic, marine bacterium Roseovarius nubinhibens ISM were interpreted such that 3-sulfolactate would be degraded as a sole source of carbon and energy for growth via a novel bifurcated pathway including two known desulfonative enzymes, sulfoacetaldehyde acetyltransferase (EC 2.3.3.15) (Xsc) and cysteate sulfo-lyase (EC 4.4.1.25) (CuyA). Strain ISM utilized sulfolactate quantitatively with stoichiometric excretion of the sulfonate sulfur as sulfate. A combination of enzyme assays, analytical chemistry, enzyme purification, peptide mass fingerprinting, and reverse transcription-PCR data supported the presence of an inducible, tripartite sulfolactate uptake system (SlcHFG), and a membrane-bound sulfolactate dehydrogenase (SlcD) which generated 3-sulfopyruvate, the point of bifurcation. 3-Sulfopyruvate was in part decarboxylated by 3-sulfopyruvate decarboxylase (EC 4.1.1.79) (ComDE), which was purified. The sulfoacetaldehyde that was formed was desulfonated by Xsc, which was identified, and the acetyl phosphate was converted to acetyl-coenzyme A by phosphate acetyltransferase (Pta). The other portion of the 3-sulfopyruvate was transaminated to (S)-cysteate, which was desulfonated by CuyA, which was identified. The sulfite that was formed was presumably exported by CuyZ (TC 9.B.7.1.1 in the transport classification system), and a periplasmic sulfite dehydrogenase is presumed. Bioinformatic analyses indicated that transporter SlcHFG is rare but that SlcD is involved in three different combinations of pathways, the bifurcated pathway shown here, via CuyA alone, and via Xsc alone. This novel pathway involves ComDE in biodegradation, whereas it was discovered in the biosynthesis of coenzyme M. The different pathways of desulfonation of sulfolactate presumably represent final steps in the biodegradation of sulfoquinovose (and exudates derived from it) in marine and aquatic environments.